Peculiarities of expression of HIF-1Α and HIF-3Α in hypothalamus of Wistar rats under the influence of intermittent hypobaric hypoxia - A. V. Abramov; V. A. Shamenko (Zaporozhye State Medical University, 2017)
The purpose of this study was to establish the features of the expression of hif‑1α and hif-3α genes and the accumulation of HIF-1α and HIF-3α proteins in the paraventricular (PVH) and supraoptic (SO) nuclei of the hypothalamus under the conditions of intermittent hypoxia and in post-hypoxic periods. Materials and methods. Intermittent hypoxia was modeled by a daily 6 hour stay of rats at an altitude of 6000 m (pO2 = 9,8%) for 15 days, the posthypoxic period was 10 days. The distribution of HIF-1α and HIF-3α proteins in the hypothalamus was investigated by immunofluorescence methods. A molecular-genetic study was carried out using polymerase chain reaction with real-time reverse transcription of mRNA expression level of the hif-1α and the hif-3α gene. Results. It was established that intermittent hypoxia led to a 13-fold increase in the mRNA level in the mediobasal hypothalamus to HIF-1α, and 8,6-fold to HIF-3α. In neurons of medial parvocellular (PVHmp) and posterior lateral magnocellular subnuclei (PVHpml) of PVH, an increase in the area of immunoreactivity to HIF-1α and to HIF-3α was observed, as well as an increase in the HIF-1α protein content of 2,5 (PVHmp) and 3,4 (PVHpml) times, and the HIF-3α protein in 1,7 and 3,0 times, respectively. In the posthypoxic period, the level of mRNA to HIF-1α and HIF-3α in the hypothalamus decreased, but for HIF-1α remained 2.5 times higher than in the control. At the same time, the content of HIF-1α and HIF-3α proteins remained increased in parvocellular neurons of PVH and decreased by 50-60% in magnocellular neurons of PVH. The reaction of neurons of SO to hypoxia was characterized by a decrease in the expression of HIF-1α and HIF 3α proteins, which was manifested by a decrease in the area of immunoreactivity in neurons partially restored in the post-hypoxic period. Conclusion. The results show that intermittent hypoxia leads to an increase in the expression of the hif gene family and to an increase in the synthesis of HIF proteins in PVH neurons and its preservation in the post-hypoxic period.